An organizational framework for the use of web-based tools in ""Virtual"" project teams - Weimann, Peter (Department of Information Systems, 2014)
The project management of virtual teams differs from that of traditional ones. Traditional project risks like complexity, the uncertainty of factors influencing the project, and the high interdependency of project tasks must be managed alongside changed temporal, geographic, and cultural dimensions. Numerous researchers have investigated the factors influencing the success of virtual teams, but little research has been done to understand how to align technology with team and project tasks. When investigating virtual team technology, mediation should be considered as a central theme, while new web-based project management tools are likely to affect project management processes, particularly for virtual teams. This thesis investigates how virtual project teams should select and use Internet/web-based tools to improve the team's performance and the satisfaction of its members. In the last three years I have observed, questioned, and interviewed 28 project teams with 167 team members in Germany and South Africa. The sampling and analyses of these teams were approached using grounded theory and aimed at developing a resultant theory. The major theoretical contribution of my research is a holistic framework relating the effects on virtual project teams of Internet/web-based tools. The goal of my research was to develop a theory to explain the selection and use of web-based tools by virtual teams operating in different contexts, and to explain and illustrate the consequences of the use of different tool combinations. My results contribute to practice by providing a number of guidelines for management of virtual teams as well as knowledge required by companies wishing to launch projects with virtual teams. Differing performances of teams can in many cases be attributed to such conditions as: limited Internet availability and bandwidth; lack of training for certain tools; the wrong selection and use of tools that are either not integrated/do not support adequate sharing among team members/do not help to manage the tasks and promote transparency about progress made. Definite areas emerged where tool selection and use, or lack of use of appropriate tools, affected performance. My theory also emphasises that besides the project and team context the personal preferences and distance from work of each member are important when selecting and using web-based tools in a distributed work setting. While communication is the heart of project teams, sharing is the soul of project teams that are virtual and use web-based tools. Task awareness is a key influencing the team members' satisfaction.